Quorum sensing restrains growth and is rapidly inactivated during domestication of Sinorhizobium meliloti. Issue 2 (24th February 2015) - Charoenpanich, Pornsri; Soto, Maria J.; Becker, Anke; McIntosh, Matthew
Summary Microbial cooperative behaviours, such as quorum sensing (QS), improve survival and this explains their prevalence throughout the microbial world. However, relatively little is known about the mechanisms by which cooperation promotes survival. Furthermore, cooperation typically requires costly contributions, e.g. exopolysaccharides, which are produced from limited resources. Inevitably, cooperation is vulnerable to damaging mutations which results in mutants that are relieved of the burden of contributing but nonetheless benefit from the contributions of their parent. Unless somehow prevented, such mutants may outcompete and replace the parent. The bacterium Sinorhizobium meliloti uses QS to activate the production of copious levels of exopolysaccharide (EPS). Domestication of this bacterium is typified by the appearance of spontaneous mutants incapable of EPS production, which take advantage of EPS production by the parent and outcompete the parent. We found that all of the mutants were defect in QS, implying that loss of QS is a typical consequence of the domestication of this bacterium. This instability was traced to several QS‐regulated processes, including a QS‐dependent restraint of growth, providing the mutant with a significant growth advantage. A model is proposed whereby QS restrains population growth to prevent overcrowding and prepares the population for the survival of severe conditions.